Divergent responses of the fall armyworm and a parasitoid to rising temperature - Shannon Alary; Manuel Massot; Véronique Jouan; Isabelle Darboux (Biological Control, 2025)
Temperature is a key factor influencing insect performance and host-parasitoid interactions. Knowing how hosts and parasitoids respond to temperature variations is crucial for predicting the success of biological control strategies, especially in the context of climate change. This study aimed to assess how developmental temperature affects the interaction between the fall armyworm (FAW) Spodoptera frugiperda, a major invasive pest, and the larval endoparasitoid Hyposoter didymator. FAW caterpillars were reared under three fluctuating temperature regimes centered at 20 °C, 25 °C, and 30 °C (± 5°C of daily variation), and were either left unexposed or exposed to H. didymator. We analyzed host survival, developmental time, and body mass, as well as the success of the parasitoid. In unparasitized FAW, higher temperatures accelerated development and increased pupal survival but reduced larval survival and adult body mass. In parasitized FAW, the proportion of individuals that survived increased at 30 °C, suggesting that higher temperatures may undermine the biological control of this pest. For H. didymator, temperature accelerated development but had negative effects at 30 °C, leading to reduced survival during the endoparasitic phase and impaired cocoon formation. These contrasting responses led to opposite trends: the multiplication rate of FAW increased with temperature, while that of the parasitoid decreased at the highest temperature. This study underscores the importance of considering the thermal sensitivity of both FAW and its potential parasitoids when designing effective and sustainable pest management strategies.